2022
DOI: 10.3390/jpm12060896
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven EEG Theta and Alpha Components Are Associated with Subjective Experience during Resting State

Abstract: The resting-state paradigm is frequently applied to study spontaneous activity of the brain in normal and clinical conditions. However, the relationship between the ongoing experience of mind wandering and the individual biological signal is still unclear. We aim to estimate associations between subjective experiences measured with the Amsterdam Resting-State Questionnaire and data-driven components of an electroencephalogram extracted by frequency principal component analysis (f-PCA). Five minutes of resting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…In this study, we investigated the behavior of the proposed LTP model with physiologically relevant interstimulus intervals. The background activity in a brain corresponds to range of frequency, rather than on the specific frequencies: the main power spectra components of electroencephalogram (EEG) recordings at rest are at frequencies < 20 Hz [28]. Single cell in vivo recordings from experimental animals revealed that spontaneous firing of neurons is highly irregular, and the average frequency depends on a cell type: 0.14 Hz in hippocampal CA1 and CA3 pyramidal cells of mice [19]), 1 Hz in L5 visual cortical pyramidal neurons of rats [18], and 4 Hz in pyramidal cells of rat prefrontal cortex [4].…”
Section: Interstimulus Interval and Bistable Ltp Model Behaviormentioning
confidence: 99%
“…In this study, we investigated the behavior of the proposed LTP model with physiologically relevant interstimulus intervals. The background activity in a brain corresponds to range of frequency, rather than on the specific frequencies: the main power spectra components of electroencephalogram (EEG) recordings at rest are at frequencies < 20 Hz [28]. Single cell in vivo recordings from experimental animals revealed that spontaneous firing of neurons is highly irregular, and the average frequency depends on a cell type: 0.14 Hz in hippocampal CA1 and CA3 pyramidal cells of mice [19]), 1 Hz in L5 visual cortical pyramidal neurons of rats [18], and 4 Hz in pyramidal cells of rat prefrontal cortex [4].…”
Section: Interstimulus Interval and Bistable Ltp Model Behaviormentioning
confidence: 99%